2008
DOI: 10.1002/mrc.2236
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR assignments of two new diaryl ethers phomopsides A and B from the mangrove endophytic fungus (ZZF08)

Abstract: Two new diaryl ethers, named phomopside A (1) and B (2), together with known excelsione (3) were isolated from the mangrove endophytic fungus Phomopsis sp. (ZZF08) obtained from the South China Sea coast. The structure of 1 was elucidated by NMR spectroscopy and confirmed by X-ray crystallography. Compounds 2 and 3 were identified by NMR spectroscopy and comparing the spectroscopic data with literature values. In addition, the plausible biogenetic path of 1, 2 and 3 is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…On comparison of the current 13 C NMR data with those in the literature, [11] it was found that δ C = 129.7 and δ C = 147.1 should be assigned to C-3 and C-8, not to C-8a and C-4a as reported. In fact the 13 C NMR signals of C-4a and C-8a were δ C = 119.5 and δ C = 136.5, respectively. The corrected assignments of 13 H and 13 C NMR are listed in Table 1.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…On comparison of the current 13 C NMR data with those in the literature, [11] it was found that δ C = 129.7 and δ C = 147.1 should be assigned to C-3 and C-8, not to C-8a and C-4a as reported. In fact the 13 C NMR signals of C-4a and C-8a were δ C = 119.5 and δ C = 136.5, respectively. The corrected assignments of 13 H and 13 C NMR are listed in Table 1.…”
Section: Resultsmentioning
confidence: 97%
“…We had observed these longer-range n J CH couplings (n > 3) in another compound. [13] Compound (4) was obtained as colorless needle crystal. EIMS at m/z 236 along with the complete analysis of NMR data (Table 1) deduced the structure of this compound as 3-hydroxymethyl-6,8-dimethoxycoumarin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many metabolites with a structural similarity to 1, such as corynesidones [12], excelsional [14], and stictic acid [17], or the phomopsides [18] have been isolated previously from lichens and fungi. However, compound 1 is the parent compound in the series of more than 60 orsellinic acid-derived depsidones and had not been described so far.…”
Section: Resultsmentioning
confidence: 99%